2019
DOI: 10.1590/0100-3984.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound in deep endometriosis: pictorial essay

Abstract: Endometriosis is characterized by the presence of endometrial tissue outside the uterus. When endometrial implants penetrate more than 5 mm into the peritoneum, the condition is referred to as deep pelvic endometriosis. Although laparoscopy is the gold standard test to establish a diagnosis of deep endometriosis, transvaginal ultrasound represents an alternative that can contribute to detection of the disease, because it is an accessible, low-cost, noninvasive examination that allows preoperative planning in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…A number of recent studies conducted in Brazil have highlighted the importance of imaging methods in the evaluation of the female reproductive system (22)(23)(24)(25)(26)(27) . The use of microCT was pivotal to observing the vasculariza tion in detail.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies conducted in Brazil have highlighted the importance of imaging methods in the evaluation of the female reproductive system (22)(23)(24)(25)(26)(27) . The use of microCT was pivotal to observing the vasculariza tion in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high cost of check, time consuming, and restricted clinical usage, in general, ultrasonic has more application value in diagnosis of DIE. Ultrasound generally fall into the abdominal ultrasound, transvaginal ultrasound by transrectal ultrasound and endoscopic ultrasonography examination (9)(10)(11)(12)(13)(14). Transvaginal ultrasound is considered as a kind of convenient safe noninvasive way to check.…”
Section: Original Articlementioning
confidence: 99%
“…Progestins Progestins inhibit the hypothalamic-pituitary-ovarian axis, reducing serum estrogen levels and leading to anovulation and atrophy of the eutopic endome-trium and endometrial lesions. They modulate the immune response involved in the pathogenesis of endometriosis, decreasing peritoneal inflammatory mediators, inhibiting angiogenesis and suppressing matrix metalloproteinases, factors that facilitate the growth and implantation of the ectopic endometrium [5]. Of this class, the main drugs and/or methods reported were: dienogest [5], medroxyprogesterone acetate [7] and norethisterone acetate [6] [7], as well as the levonorgestrel-releasing system (LGN-IUS) and the etonogestrel-releasing implant [25].…”
Section: Hormonal Pharmacological Therapiesmentioning
confidence: 99%
“…It was found that dienogest, a 4th generation selective progesterone, composed of 19-nortestosterone and progesterone derivatives, has low androgenic, estrogenic, glucocorticoid and/or mineralocorticoid activities. In addition, it has anovulatory, antiproliferative effects and inhibits the secretion of cytokines in the stroma of endometrial cells [5]. Dienogest (2 mg/day) suppressed pain about 24 weeks after starting treatment, in addition to reducing bone mineral loss observed with the use of leuprolide acetate [7].…”
Section: Hormonal Pharmacological Therapiesmentioning
confidence: 99%
See 1 more Smart Citation